Framing metamemory judgments: judgments of retention intervals (JORIs) - Tauber, Sarah K., author; Rhodes, Matthew, advisor; McCabe, David, committee member; Kraiger, Kurt, committee member; Rickey, Dawn, committee member (Colorado State University. Libraries, 2010)
Prior research has shown that participants’ predictions of memory performance are not sensitive to the time between study and test. However, this work has largely relied in one metacognitive measure, Judgments of Learning (JOLs), to assess such awareness. Thus, in three experiments I explored a new metacognitive measure. Judgments of Retention Interval (JORIs), in which participants determine how long (in minutes) information will be remembered. Results demonstrated that the metacognitive measure itself influences assessments of monitoring and control. For example participants chose to restudy more items when JORIs were made, compared with fewer restudy choices from participants who made JOLs (Experiment 2). However, participants demonstrated difficulty incorporating information about a retention interval into their judgments regardless of the type of judgment made (i.e., JOLs or JORIs). Results are considered within existing theoretical frameworks. I suggest that the metacognitive measure needs to be considered in order to accurately assess metacognitive awareness, and additional work is needed to assess metacognitive awareness of RI.
Covers not scanned.
Keywords: Metacognition; Judgment